2023
DOI: 10.1080/00325899.2023.2170848
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods for characterising the steel cleanness in powder metallurgical high-speed steels

Abstract: Powder metallurgical (PM) steels are characterised by a very high cleanness level. Single mesoscopic inclusions can nevertheless induce material failure under the extreme exposed stresses in the final product. Extensive knowledge about the cleanness of these steels is therefore essential. Various methods for inclusion analyses are available, providing different information about the non-metallic inclusion population present in the steel matrix. Several state-of-the-art methods of inclusion analysis are compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The HSS produced by powder metallurgy (PMHSS) can effectively solve the problem of structure segregation and is conducive to the uniform dispersion of carbide in the matrix, with the advantages of uniform structure, small grains and less inclusions, greatly improving the mechanical properties, and service life. [10][11][12][13] The PMHSS is first to prepare raw material powder, and subsequent powder forming, sintering, and densification.…”
Section: Introductionmentioning
confidence: 99%
“…The HSS produced by powder metallurgy (PMHSS) can effectively solve the problem of structure segregation and is conducive to the uniform dispersion of carbide in the matrix, with the advantages of uniform structure, small grains and less inclusions, greatly improving the mechanical properties, and service life. [10][11][12][13] The PMHSS is first to prepare raw material powder, and subsequent powder forming, sintering, and densification.…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 ] Furuya et al enhanced the microstructure of Cr‐Mo‐W‐V‐Co high‐speed steel using hot isostatic pressing (HIP), significantly improving the toughness and strength by 50%. [ 19 ] SPS offers distinct advantages over traditional methods such as hot pressing and HIP. Marnier et al showed that the preparation of 316L stainless steel samples using SPS yields significantly finer grains along with enhanced hardness and corrosion resistance as compared with those produced by casting.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to a high tendency of crack initiation at the phase boundary steel-NMI which means that NMIs can decrease fatigue strength drastically. [17] Schickbichler et al [18] performed high cycle fatigue (HCF) tests with high-alloyed steels and showed that large NMIs initiated the fracture during these HCF tests. Moreover, near-surface NMIs decrease the quality of polished surfaces and change the optical appearance which is an issue especially for automotive sheets.…”
Section: Introductionmentioning
confidence: 99%